A room with a view: excavations at Ravelrig Quarry - Rennie, Christine; Ramsey, Susan; Ballin, Torben Bjarke; Ballin Smith, Beverley (Proceedings of the Society of Antiquaries of Scotland, 2014)
Excavations at Ravelrig Quarry, City of Edinburgh revealed activity from the Late Neolithic, and late Bronze Age, although the main phase of activity was the construction of a palisaded homestead during the early Iron Age. Inside an oval shaped palisade was a circular ring-groove roundhouse and a possible second circular structure comprising ditches and post-holes. The roundhouse contained a central hearth with associated post-holes, two large pits and features that appear to represent the early formation of a ring-ditch. This phase has been radiocarbon dated to 600–400 cal BC